2015
DOI: 10.1016/j.ijdevneu.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 exerts neuroprotective effects in an ex vivo model of mild hyperhomocysteinemia

Abstract: Elevated plasma homocysteine (Hcy) levels have been detected in patients with various neurodegenerative conditions. Studies of brain tissue have revealed that hyperhomocysteinemia may impair energy metabolism, resulting in neuronal damage. In addition, new evidence has indicated that vitamin D plays crucial roles in brain development, brain metabolism and neuroprotection. The aim of this study was to investigate the neuroprotective effects of 1,25-dihydroxivitamin D3 (calcitriol) in cerebral cortex slices that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…This enzyme belongs to the first line of cellular defense against oxidative injury and has been observed to be diminished in the hHcy group compared to the control group. These results are consonant with very recent experiments of Longoni et al (2016), which also emphasize a high potency of hHcy conditions for putative posttranslational Hcy induced protein modifications. This likely could lead to enzyme(s) homocysteinylation and thiolation which might contribute to the partial enzyme inactivation.…”
Section: Toxicity Of Homocysteine To Neural Cells As a Stroke Risk Fasupporting
confidence: 91%
See 1 more Smart Citation
“…This enzyme belongs to the first line of cellular defense against oxidative injury and has been observed to be diminished in the hHcy group compared to the control group. These results are consonant with very recent experiments of Longoni et al (2016), which also emphasize a high potency of hHcy conditions for putative posttranslational Hcy induced protein modifications. This likely could lead to enzyme(s) homocysteinylation and thiolation which might contribute to the partial enzyme inactivation.…”
Section: Toxicity Of Homocysteine To Neural Cells As a Stroke Risk Fasupporting
confidence: 91%
“…Similarly, results from hHcy experiments (Longoni et al, 2016) pointed out the neuroprotective effect of vitamin D (calcitriol) against hHCy as an important factor of brain development, brain metabolism and neuroprotection. The authors showed that pre-treatment with calcitriol up to 250 nmol/l has a remarkable protective effect on cortical slices.…”
Section: Toxicity Of Homocysteine To Neural Cells As a Stroke Risk Famentioning
confidence: 89%
“…In vitro studies on cerebral cortices from rats pre-treated with calcitriol and exposed to a mild concentration of homocysteine, demonstrated that altered bioenergetics parameters and impaired mitochondrial functions promoted by homocysteine were significantly attenuated by pre-treatment with calcitriol. Specifically, calcitriol reduced the concentration of ROS and lipid peroxidation and increased the antioxidant enzyme activity, preventing changes in mitochondrial brain cell [89]. This same protective antioxidant effect of vitamin D against hyperhomocysteinemia was observed in heart tissue, where the accumulation of homocysteine may contribute to the development of cardiovascular disease [90].…”
Section: Effects Of Vitamin D In the Attenuation Of Mitochondrial Oximentioning
confidence: 72%
“…However, doses up to 10 000 IU have not been shown to cause toxicity in healthy individuals [36]. Recently, there are several studies that showed calcitriol acts as a mitochondrial protective agent and antioxidant, preventing the oxidative damage induced by homocysteine in rats [26,37]. Despite the life-threatening cardiotoxicity of DIC, up to date, there is no known reversal agent for cardiotoxicity induced by DIC.…”
Section: Discussionmentioning
confidence: 99%